Communicating Technique in Teaching Speaking: Learning Opportunity and Students’ Perceptions - Muhammad Husnu; Muh Alfi Efendi; Elda Silvianti (Institut Agama Islam Negeri Palopo, 2022)
This research was carried out with the aim of expressing perceptions and improving students' English speaking skills to be more intense and active by using the communicating technique method. This study used an experimental method and an analysis of student cognition integrated with the quantitative and qualitative research methods using oral trials. The means of this study are pre-testing, treatment, post-testing, interviews, and observations. Analytical techniques used when processing data in Statistical Package for Social Sciences 22.0 for Windows. The test results before applying the communicating techniques were only 60% of students had the ability to speak English but after the application of the communicating technique. It increased to 90% of students’ ability to speak English. In analyzing student perceptions, the research result showed that the communicating techniques were effective in improving students’ ability in English. The application of the communicating techniques in learning English, especially in speaking skills, is the right strategy to improve students’ abilities because these techniques can turn abstract concepts into reality in the classroom.